Asynchronous Multimodal Text Entry Using Speech and Gesture Keyboards - Maniraj, V; Manohari, E (International Journal of Computer Sciences and Engineering, 2015)
We propose plummeting errors in text entry by uniting speech and gesture keyboard input. We describe a combine model that combines gratitude conorders in an asynchronous and flexible manner. We composed speech and gesture data of manipulators entering both short email sentences and web search queries. By amalgamation gratitude conorders from both modalities, word error rate was abridged by 53% comparative for email sentences and 29% comparative for web searches. For email exclamations with speech errors, we examined providing gesture keyboard alterations of only the mistaken words. Deprived of the user openly indicating the improper words, our model was able to decrease the word error rate by 44% relative.